TEACHING ENGLISH FOR PROFESSIONAL PURPOSES (EPP) VS CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL):THE CASE OF PLEKHANOV RUSSIAN UNIVERSITY OF ECONOMICS (PRUE) - Gavrilova, Elena; Trostina, Kira (European Scientific Journal, ESJ, 2014)
This article intends to explore the special aspects of Teaching English for Professional Purposes (EPP) and Content and Language Integrated Learning (CLIL) at Plekhanov Russian University of Economics (PRUE), one of the biggest and oldest economic universities in the Russian Federation. The paper adopts both quantitative and qualitative methodology approaches, i.e. it applies statistical data collected during the research and literature review in order to highlight the benefits and opportunities of both approaches as well as the problem areas in teaching professional English at the university level. It also focuses on the controversies faced by EPP and CLIL teachers and investigates how well current programmes and curricula satisfy both the teachers’ and students’ needs. The paper advocates that only integrated interdisciplinary approach between language and academic subject studies can result in synergy needed to prepare highly-qualified specialists in a particular field of economics.